PROFIL EMPATI MAHASISWA ETNIS JAWA (Survei Yang Dilakukan Pada Mahasiswa Jurusan Bimbingan Dan Konseling Universitas di DKI Jakarta) - Pemi Senja Maulana; Michiko Mamesah; Happy Karlina Marjo (Program Studi Bimbingan dan Konseling, Universitas Negeri Jakarta, 2015)
The porpuse of this research was to find out description aboutthebasicempathy’s students college of Guidance and Counselingfrom Java ethnic in DKI Jakarta. This research used a descriptive study with 112 respondent of students college of Guidance and Counselingfrom5UniversitiesinJakarta; Universitas Negeri Jakarta (UNJ), Universitas Muhammadiyah Prof.DrHamka Jakarta (UHAMKA), Universitas IslamAs-Syafi’iyah Jakarta, Universitas Atma Jaya and Universitas Kristen Indonesia (UKI). The research instrument used Basic Empathy Scale (BES) from Darrick Jollife dan David P Farrington (2006) with r 0.857. The valid and reliability test used SPSS version17.0. The Valid test from 20 statements there were 17 valid statements and 3 statements are drop. The drop statements rechanged to be a new editorial statements. The reliability test obtained 0,803 which means it very high reliability and the basic empathy scale can be trust.. This study has found condition of emphaty of students counseling in Jakarta at the high level categoryof 53,57%, middle category of 46,43%, and0 % lower. From these findings that there are students at middle level category, these need to improvement and development of empathy students’ condition such as using audiovisual media (movie) or roleplay method in guding service